Rhizosphere response to nickel in a facultative hyperaccumulator. (October 2019) - Rosatto, Stefano; Roccotiello, Enrica; Di Piazza, Simone; Cecchi, Grazia; Greco, Giuseppe; Zotti, Mirca; Vezzulli, Luigi; Mariotti, Mauro
Abstract: This study faces the characterization of the culturable microbiota of the facultative Ni-hyperaccumulator Alyssoides utriculata to obtain a collection of bacterial and fungal strains for potential applications in Ni phytoextraction. Rhizosphere soil samples and adjacent bare soil associated with A. utriculata from serpentine and non-serpentine sites were collected together with plant roots and shoots. Rhizobacteria and fungi were isolated and characterized genotypically and phenotypically. Plants and soils were analyzed for total element concentration using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Serpentine and non-serpentine sites differ in terms of elements concentration in soil, plant roots and shoots. Ni and Co are significantly higher on serpentine site, while Ca is more abundant in non-serpentine site. Bacteria and fungi were significantly more abundant in rhizosphere than in bare soil and were dominated by genera Arthrobacter, Bacillus and Streptomyces, Penicillium and Mucor. The genus Pseudomonas was only found in rhizospheric serpentine soils (<2% of total serpentine isolates) and with Streptomyces sp. showed highest Ni-tolerance up to 15 mM. The same occurred for Trichoderma strain, belonging to the harzianum group (<2% of the total microfungal count) and Penicillium ochrochloron (<10% of the total microfungal count, tolerance up to Ni 20 mM). Among serpentine bacterial isolates, 8 strains belonging to 5 genera showed at least one PGPR activity (1-Aminocyclopropane-1-Carboxylic Acid (ACC) deaminase activity, production of indole-3-acetic acid (IAA), siderophores and phosphate solubilizing capacity), especially genera Pantoea, Pseudomonas and Streptomyces . Those microorganisms might thus be promising candidates for employment in bioaugmentation trials. Highlights: Only 10% of hyperaccumulators have their rhizosphere examined. A. utriculata is a facultative Ni-hyperaccumulator that thrives in serpentine soils. Rhizobiota of A. utriculata seems to be limited by serpentine soil conditions. Pseudomonas, Streptomyces, T. harzianum group and P. ochrochloron hypertolerate Ni. Rhizobiota with PGP traits and high Ni tolerance can improve plant phytoextraction.